Assembly language step by step : programming with Linux - Duntemann, Jeff. (Indianapolis, Indiana : Wiley Publishing Incorporation, 2009)
The eagerly anticipated new edition of the bestselling introduction to x86 assembly language The long-awaited third edition of this bestselling introduction to assembly language has been completely rewritten to focus on 32-bit protected-mode Linux and the free NASM assembler.
Introduction: "Why Would You Want to Do That?" Chapter 1 Another Pleasant Valley Saturday. Chapter 2 Alien Bases. Chapter 3 Lifting the Hood. Chapter 4 Location, Location, Location. Chapter 5 The Right to Assemble. Chapter 6 A Place to Stand, with Access to Tools. Chapter 7 Following Your Instructions. Chapter 8 Our Object All Sublime. Chapter 9 Bits, Flags, Branches, and Tables. Chapter 10 Dividing and Conquering. Chapter 11 Strings and Things. Chapter 12 Heading Out to C. Conclusion: Not the End, But Only the Beginning. Appenix A Partial x86 Instruction Set Reference. Appendix B Character Set Charts. Index.
Includes bibliographical references and index.
Keywords: ASSEMBLY LANGUAGE (ELECTRONIC COMPUTERS)